2006
DOI: 10.1038/sj.leu.2404255
|View full text |Cite
|
Sign up to set email alerts
|

Notch and Wnt signaling in T-lymphocyte development and acute lymphoblastic leukemia

Abstract: Many acute lymphoblastic leukemias can be considered as malignant counterparts of cells in the various stages of normal lymphoid development in bone marrow and thymus. T-cell development in the thymus is an ordered and tightly controlled process. Two evolutionary conserved signaling pathways, which were first discovered in Drosophila, control the earliest steps of T-cell development. These are the Notch and Wnt-signaling routes, which both are deregulated in several types of leukemias. In this review we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 124 publications
1
66
0
1
Order By: Relevance
“…For colon carcinoma, aberrations in Wnt signaling are causative factors that have also been proposed and are increasingly seen in hematological malignancies (reviewed in Refs. 32,33 ). Cluster 5 contains only 21 genes mainly involved in cell cycle regulation (14 of 21 genes), including TOP2A (3-fold upregulated in relapsed samples), encoding a DNA topoisomerase, that controls and alters the topologic states of DNA during transcription and is often upregulated in a wide variety of cancers; and KIF 11 (2.1-fold up), a kinesin family member 11 motor protein that controls spindle dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…For colon carcinoma, aberrations in Wnt signaling are causative factors that have also been proposed and are increasingly seen in hematological malignancies (reviewed in Refs. 32,33 ). Cluster 5 contains only 21 genes mainly involved in cell cycle regulation (14 of 21 genes), including TOP2A (3-fold upregulated in relapsed samples), encoding a DNA topoisomerase, that controls and alters the topologic states of DNA during transcription and is often upregulated in a wide variety of cancers; and KIF 11 (2.1-fold up), a kinesin family member 11 motor protein that controls spindle dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…146 Cooperation between Wnt and Notch in HSCs has recently been suggested by Duncan et al 89 Furthermore, studies have demonstrated a role for Wnt and Notch in T-cell leukemias. 147 For example, Weng et al 148 could show that over 50% of human T-ALL patients have activating mutations in Notch1. Deregulated T-cell proliferation might result from suppression of p53 and/or activation of the NF-kB by Notch.…”
Section: Other Mechanisms Of Aberrant Wnt Signaling In Amlmentioning
confidence: 99%
“…At least half of all human T-ALL carry activating mutations in the intracellular part of Notch1. 17,18 To develop into a T cell, Notch signaling is clearly indispensable, but the downstream mechanisms by which a Notch signal is translated into a T-cell program are still largely unclear. The best known Notch target genes are Hairy-Enhancer of Split (HES)1 and HES5 and Hes-related repressor protein (HERP).…”
Section: Introductionmentioning
confidence: 99%